Bedside Interprofessional Rounding: The View From the Patient's Side of the Bed. (March 2017) - Burdick, Kailee; Kara, Areeba; Ebright, Patricia; Meek, Julie
Background: Bedside interprofessional rounding is gaining ground as a means to improve collaboration and patient outcomes, yet little is known regarding patients' perceptions of the practice. Methods: This descriptive study used individual patient interviews to elicit views on interprofessional rounding from 35 patients at a large, urban hospital. Results: The findings identified three major categories: 1) about the rounding process; 2) clinical information; and 3) the impact/value of bedside inter-professional rounding. Discussion: Intentionally eliciting and responding to our patients' views of interprofessional rounding may help us design methods that are patient centered and effective.